Erratum: Fission and fusion scenarios for magnetic microswimmer clusters - Francisca Guzmán-Lastra (Nature Portfolio, 2017)
Nature Communications 7: Article number: 13519 (2016); Published 22 November 2016; Updated 17 January 2017 This Article contains an error in Reference 18 that was introduced during the production process. The correct reference should be: Steinbach, G. et al. Stirrers and movers actuated by oscillating fields.